2022
DOI: 10.1155/2022/6781650
|View full text |Cite
|
Sign up to set email alerts
|

Bank Credit Financing and Trade Credit Financing Based on Carbon Emission Trading

Abstract: Bank credit financing and trade credit financing are two basic ways for small- and medium-sized enterprises to solve financial difficulties. We studied a supply chain financing (SCF) system with one capital-constrained manufacturer and one capital-rich supplier, in which manufacturers can choose bank credit financing (BCF) or trade credit financing (TCF) to solve financial difficulties. Unlike the traditional SCF, we considered the influence of the carbon emission trading mechanism, and we designed BCF and TCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Cao and Yu (2019) buttressed that only a limited number of lenders possess the necessary expertise to provide loans for carbon finance, typically at higher interest rates compared to those found in a perfectly competitive lending market. The allocation of funds by financial institutions plays a significant role in guiding the development of enterprises, including their efforts in carbon emissions control (Sun & Gao, 2022; Zhang et al, 2022; Zhou & Li, 2019). In the process of allocating funds, financial organizations can take on environmental and social responsibilities.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cao and Yu (2019) buttressed that only a limited number of lenders possess the necessary expertise to provide loans for carbon finance, typically at higher interest rates compared to those found in a perfectly competitive lending market. The allocation of funds by financial institutions plays a significant role in guiding the development of enterprises, including their efforts in carbon emissions control (Sun & Gao, 2022; Zhang et al, 2022; Zhou & Li, 2019). In the process of allocating funds, financial organizations can take on environmental and social responsibilities.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Lo (2016) revealed that financial institutions show reluctance in participating in the carbon market. Enterprises require external financing to attain their objectives of reducing carbon emissions and adopting low‐carbon practices (Sun & Gao, 2022). The involvement of financial institutions is crucial in enhancing the financial characteristics of the carbon market.…”
Section: Discussion Of Clustered Factors On Barriers To the Adoption ...mentioning
confidence: 99%
See 1 more Smart Citation
“…And climate change caused by carbon emissions has received great attention from countries around the world [2,3]. Many countries and regions around the world have taken positive measures to reduce carbon emissions, among which regional low-carbon innovation capability is one of the important indicators [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…For Sun & Gao (2022), many countries and regions have enacted various policies to limit carbon emissions to control carbon emissions, among which the carbon emissions trading policy is the most widely used. Carbon emissions trading refers to companies in the same sector; if the company's actual carbon emission is less than the government's quota by increasing research and technological innovation, the company can sell the extra quota in the market to make profits; on the contrary, if a company's carbon emissions exceed the quota, it will need to buy the remaining quota from other companies in the market to continue production.…”
mentioning
confidence: 99%